(untitled) (Research, Society and Development, 2022)
Objective: To analyze the anthropometric parameters used as alternatives to identify visceral fat and cardiovascular risk in patients with hepatitis C. Methodology: Study carried out between June to November of 2017, with hepatitis C patients. Social data, lifestyle and biochemical parameters were collected. Anthropometric assessment was carried out, being measured height, weight, waist circumference and hip circumference were measured. Then, body mass index, waist and height ratio, waist-to-hip ratio, visceral adiposity index and Framinghan risk score were calculated. For statistical analysis, chi-square test was applied, and simple and multiple logistic regressions have been performed to explore the correlation between anthropometric parameters and Framingham risk score, adopting a 5% significance level. Statistical Package for Social Science software was used. Results: 55 patients evaluated. It was observed that 56.36% presented cardiovascular risk according to waist circumference and waist-to-hip ratio, 78.18% according to the waist and height ratio, and 74.55% according to the visceral adiposity index. In the relation between Framingham risk score and anthropometric parameters it was observed that waist-to-hip ratio was considered a significant independent predictor (OR=14.7000; CI95% = 3.5360 – 61.1180). Conclusion: For the identification of visceral fat, it is suggested to use the waist-to-hip ratio because it indicated a probability for the development of cardiovascular events in individuals with hepatitis C.